2018
DOI: 10.1029/2018gl078193
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Composition Dependence of Sea Spray Aerosol Production

Abstract: A discrepancy between laboratory and field‐derived parameterizations for the dependence of sea spray aerosol (SSA) particle number concentrations (Np) and size distributions on water temperature (Tw) exists. Here we address this discrepancy by quantifying the Tw dependence of SSA production over the range −2–25 °C for laboratory‐generated particles using a marine aerosol reference tank (MART), a miniature MART (miniMART), and a plunging jet. Four water types were considered: NaCl water, reef salt (RS) water, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 41 publications
5
67
3
Order By: Relevance
“…Along with Jaeglé et al (2011), other studies have found that SSA concentrations are correlated with sea surface temperature (Mårtensson et al, 2003;Sellegri et al, 2006;Sofiev et al, 2011;Grythe et al, 2014). More recently, Forestieri et al (2018) demonstrated that variability in seawater composition may have just as large an impact on SSA production as temperature. Nonetheless, our results demonstrate that for the Southern Ocean during winter when SSA is the dominant contributor to AOD, reducing the wind speed dependency of SSA production results in good agreement between the model and observations.…”
Section: Simulated Sea Salt Aerosolmentioning
confidence: 79%
“…Along with Jaeglé et al (2011), other studies have found that SSA concentrations are correlated with sea surface temperature (Mårtensson et al, 2003;Sellegri et al, 2006;Sofiev et al, 2011;Grythe et al, 2014). More recently, Forestieri et al (2018) demonstrated that variability in seawater composition may have just as large an impact on SSA production as temperature. Nonetheless, our results demonstrate that for the Southern Ocean during winter when SSA is the dominant contributor to AOD, reducing the wind speed dependency of SSA production results in good agreement between the model and observations.…”
Section: Simulated Sea Salt Aerosolmentioning
confidence: 79%
“…Alpert et al (2015) showed an increase in the number flux of up to three times in actively growing bacteria and phytoplankton mesocosm experiments while Christiansen et al (2019) showed a decrease in the number production flux with increases in algal biomass. Tyree et al (2007) and Forestieri et al (2018) reported mixed responses of the number production flux when including organic matter. This is clearly an area for further study.…”
Section: Ssa Emission Fluxmentioning
confidence: 99%
“…Multimodel assessments (Collins et al, 2017) are ongoing to characterize the spread in sea salt feedbacks across current climate models. Future work will aim at leveraging recent field and laboratory observational constraints (Bian et al, 2019;Forestieri et al, 2018;Saliba et al, 2019) on the response of sea salt to temperature. Of particular importance is the response of the sea salt size distribution to warming with recent experiments showing an increase sensitivity with size, which may modulate both the sea salt direct effect and the contribution of sea salt to the cloud condensation nuclei population (Forestieri et al, 2018;Modini et al, 2015;Partanen et al, 2014;Saliba et al, 2019;Quinn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Future work will aim at leveraging recent field and laboratory observational constraints (Bian et al, 2019;Forestieri et al, 2018;Saliba et al, 2019) on the response of sea salt to temperature. Of particular importance is the response of the sea salt size distribution to warming with recent experiments showing an increase sensitivity with size, which may modulate both the sea salt direct effect and the contribution of sea salt to the cloud condensation nuclei population (Forestieri et al, 2018;Modini et al, 2015;Partanen et al, 2014;Saliba et al, 2019;Quinn et al, 2017). Our work also highlights that changes in sea salt lifetime with warming as well as the representation of AMOC and low-level clouds, all of which remain uncertain (Bony & Dufresne, 2005;Cheng et al, 2013;Struthers et al, 2013), also play important roles in modulating how changes in sea salt impact climate sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation